Inhibition of acetylpolyamine and spermine oxidases by the polyamine analogue chlorhexidine. (June 2013) - Cervelli, Manuela; Polticelli, Fabio; Fiorucci, Laura; Angelucci, Emanuela; Federico, Rodolfo; Mariottini, Paolo
<x xml:space="preserve">Abstract</x> Acetylpolyamine and spermine oxidases are involved in the catabolism of polyamines. The discovery of selective inhibitors of these enzymes represents an important tool for the development of novel anti-neoplastic drugs. Here, a comparative study on acetylpolyamine and spermine oxidases inhibition by the polyamine analogue chlorhexidine is reported. Chlorhexidine is an antiseptic diamide, commonly used as a bactericidal and bacteriostatic agent. Docking simulations indicate that chlorhexidine binding to these enzymes is compatible with the stereochemical properties of both acetylpolyamine oxidase and spermine oxidase active sites. In fact, chlorhexidine is predicted to establish several polar and hydrophobic interactions with the active site residues of both enzymes, with binding energy values ranging from −7.6 to −10.6 kcal/mol. In agreement with this hypothesis, inhibition studies indicate that chlorhexidine behaves as a strong competitive inhibitor of both enzymes, values of Ki being 0.10 μM and 0.55 μM for acetylpolyamine oxidase and spermine oxidase, respectively.